OPTIMAL CHANNEL ALLOCATION IN CELLULAR SYSTEMS (Journal of Information and Communication Technology, 2003)
We address the problem of determining the optimal number of reserved and unreserved channels in cellular networks with integrated voice/data traffic. Four prioritized channel assignment schemes are considered for which the optimal number of channels for different traffic is determined. In scheme 1 (CAS 1), a fixed number of channels are reserved especially to serve hand-off calls. Scheme 2 (CAS 2) provides a buffer to the hand-off voice calls so that they could be served when the channel gets free. In scheme 3 (CAS 3), the new calls are allowed to use the reserved channels also, if they are available. In order to cope with the heavy traffic conditions, the reserved channels are subrated to accommodate more voice users in scheme 4 (CAS 4). The optimal number of channels to be allocated to each cell in all the schemes is calculated using an iterative algorithm, which minimizes the overall blocking probability of the handoff calls by solving a non-linear integer-programming problem. All the schemes are compared in terms of blocking probabilities of hand-off calls and new calls, overall blocking probability and carried load by using numerical illustrations.